Proceedings of the URECA@NTU 2007-2008 - Students of URECA Programme (2024)
Proceedings of the URECA@NTU 2007-08 is a compilation of selected URECA research papers, submitted by the URECA students of 2007-08, co-authored with their respective URECA professors.